2021
DOI: 10.4103/jpbs.jpbs_232_19
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Phytochemical and Biological Activities

Abstract: A BSTRACT Ficus deltoidea Jack (Moraceae) is a well-known medicinal plant used in customary medication among the Malay people to reduce and mend sicknesses such as ulcers, psoriasis, cytotoxicity, cardioprotective, inflammation, jaundice, vitiligo, hemorrhage, diabetes, convulsion, hepatitis, dysentery injuries, wounds, and stiffness. Ficus deltoidea contains a wide variety of bioactive compounds from different phytochemical groups such as alkaloids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…The methanol extract showed the lowest MIC value (3.125 mg/mL) and the widest inhibition zone (15.67 mm) against the growth of S. aureus. B. subtilis had the highest MIC value (25 mg/mL) and the lowest sensitivity (6.33 mm) to the chloroform extract [5]. At 50 and 100 mg/mL, the MIC and minimum fungicidal concentration (MFC) for Candida albicans were both achieved with the studied extracts.…”
Section: Effects On Microorganismsmentioning
confidence: 96%
See 2 more Smart Citations
“…The methanol extract showed the lowest MIC value (3.125 mg/mL) and the widest inhibition zone (15.67 mm) against the growth of S. aureus. B. subtilis had the highest MIC value (25 mg/mL) and the lowest sensitivity (6.33 mm) to the chloroform extract [5]. At 50 and 100 mg/mL, the MIC and minimum fungicidal concentration (MFC) for Candida albicans were both achieved with the studied extracts.…”
Section: Effects On Microorganismsmentioning
confidence: 96%
“…The smallest reported sensitivity to chloroform extract was 6.33 mm, while the largest MIC was 25 mg/mL, both for B. subtilis [52]. Except for chloroform and aqueous extracts of B. subtilis, E. coli, and P. aeroginosa, all extracts demonstrated inhibitory effects on the fungi, Gram-positive and Gram-negative bacteria [5]. Results showed that the methanol extract was effective against the bacteria and the fungi used in the tests.…”
Section: Effects On Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…With branches that were around 15-22 feet high and 3-10 feet wide, it frequently reached a height of 22 feet. Te bark and trunk were commonly grey and thin, respectively [91]. In conventional medicine, they had been used as a carminative, stomachic, microbicide, in postural hypotension, and as an antidysentery medication.…”
Section: Hauili Hauili Also Known As Ficus Septica (Familymentioning
confidence: 99%
“…Phytochemical compounds such as alkaloids, terpenes, saponins, flavonoids, and steroids were detected [7,8]. The biological studies had been done on the leaves, stem, bark, root, and fruit [9][10][11]. Fig.…”
Section: Introductionmentioning
confidence: 99%